Hadis-Hadis Akhlak dalam Kitab al-Majalis al-Saniyyah fi al-Kalam ‘ala Arba’in al-Nawawiyah: Studi Kitab Syarah Hadis di Pesantren - Khoirul Imam; Muhammad Zuhdi Nadzif; Muhsin Khoirul Fata (IIQ An Nur Yogyakarta, 2023)
The practice of Islamic teachings related to morals is one of the aspects emphasized in education at Islamic boarding schools. This article examines the moral hadiths contained in the book al-Majalis al-Saniyyah fi al-Kalam 'ala Arba'in al-Nawawiyah as the yellow book which is still taught in Islamic boarding schools. The book includes explanations from the book Arbain Nawawi, where this book is also widely taught in Islamic boarding schools in Indonesia, It contains a collection of hadith related to faith, fiqh and the majority of morals. The method used is descriptive-analytical with a book analysis study approach (bahsu al-kutub) to find out: (1) what is the urgency of teaching the book in Islamic boarding schools, (2) what are the systematics and methods used and (3) what are the hadiths? morals contained in the book and how the author of the book explains the meaning of the hadiths. This article finds that; First, this book needs to continue to be taught because the matan hadith book, namely Arbain Nawawi, has not explained the meaning contained in the hadith. Second, the systematic writing follows the systematic writing of the book Arbain Nawawi and the method used is the tahlili method. Third, in this book, there are 24 hadiths related to morals. When explaining the meaning of hadith, the book's author includes verses from the Koran, the hadiths of the Prophet SAW. others with the same theme, as well as mentioning the benefits and useful stories related to the hadith theme.